Developing Annuities Markets : The Experience of Chile - Rocha, Roberto (Washington, DC: World Bank, 2012)
Demographic aging strains pension systems around the world, leading frequently to large pension expenditures and deficits. The increasing awareness of a looming pension crisis has led to a wave of pension reforms, particularly in the last decade. The purpose of the report is to examine the Chilean experience in developing the market for retirement products, including programmed or phased withdrawals (PWs) and annuities, and to draw lessons for other countries that are also making efforts to develop such markets or anticipate the need to do so. The report examines the performance of the market and the evolution of the regulatory framework since the implementation of the pension reform of 1981, but with a focus on the past 10 years.